Exclusive Breastfeeding Education for Pregnant Women to Help Reduce Stunting in Selebung Village, Batukliang District - Yulastini, Fitria; Hidayati, Diah Ulfa (Edujavare Publishing, 2025)
Stunting is a serious nutritional problem in Indonesia that can hinder children's physical and cognitive development. Based on data on the prevalence of stunting in toddlers collected by WHO, Indonesia is among the third countries with the highest prevalence in the Southeast Asia region. One effective effort to prevent stunting is to provide exclusive breastfeeding to babies from birth in accordance with one of the goals of the SDG's (Sustainable Development Goals) program, namely ending all forms of malnutrition with a strategic plan (renstra) to increase the percentage of babies under 6 months who receive exclusive breastfeeding. This community service activity aims to provide education about Exclusive Breastfeeding for pregnant women as an effort to reduce the incidence of stunting. This community service method uses Participatory Rural Appraisal (PRA) with educational counseling techniques assisted by flip sheet media. The target of this community service activity is pregnant women at the Polindes in Selebung Village, Aik Darek Health Center, Batukliang District, Central Lombok Regency. The results of this community service activity show an increase in pregnant women's understanding of Exclusive Breastfeeding. It is hoped that by increasing the knowledge and awareness of pregnant women, there will be a decrease in stunting rates in Selebung Village, as well as improving the quality of maternal and child health in the area.